2015
DOI: 10.4314/ahs.v15i2.33
|View full text |Cite
|
Sign up to set email alerts
|

Pattern & presentation of colorectal cancer in central Sudan, a retrospective descriptive study, 2010-2012.

Abstract: Aims & objective: To determine the age and gender distribution and clinical presentation of patients together with histological types of colorectal cancer cases presented to Ibn Sina specialized hospital. Patients and methods: This retrospective study was conducted in Ibn Sina Hospital (Sudan). Seventy three (73) patients of colorectal cancer who presented in the period from January 2010 to December 2012 were included. Data were collected from their hospital records and analyzed using SPSS computer program 17.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
12
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 12 publications
4
12
3
Order By: Relevance
“…11 However, Taha et al, also reported rectal bleeding to be the most common presenting symptom accounting for 71.7% and a study conducted in Wad Medani Hospital in Sudan described rectal bleeding as the most common presenting symptom in 97.2% patients. 12 In our study however, none of the patients presented with tenesmus as the presenting symptom but in many studies tenesmus was one of the chief complaints in the patients with colorectal carcinoma. A study conducted in Sudan by Taha et al, shows that around 32% patients had tenesmus.…”
Section: Discussioncontrasting
confidence: 59%
See 4 more Smart Citations
“…11 However, Taha et al, also reported rectal bleeding to be the most common presenting symptom accounting for 71.7% and a study conducted in Wad Medani Hospital in Sudan described rectal bleeding as the most common presenting symptom in 97.2% patients. 12 In our study however, none of the patients presented with tenesmus as the presenting symptom but in many studies tenesmus was one of the chief complaints in the patients with colorectal carcinoma. A study conducted in Sudan by Taha et al, shows that around 32% patients had tenesmus.…”
Section: Discussioncontrasting
confidence: 59%
“…A study conducted in Sudan by Taha et al, shows that around 32% patients had tenesmus. 12 Abdalla et al however in his study reported that of 35% of the patients who presented in the emergency department, 94.8% had an acute or sub acute intestinal obstruction. 13 In conclusion, colorectal cancer was found to affect younger age groups, but with the peak incidence in patients above the age of 45 years.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations